Attitudes, Acceptance, and Willingness to Pay for The Covid-19 Vaccine: A Case Study of Magelang, Indonesia - Efendi Aqila P H; Santoso Setiyo Budi; Pribadi Prasojo (BIO Web of Conferences, 2024)
Various efforts have been made to suppress the spread of Covid-19, one of which is creating a vaccine. However, as this vaccination progresses, there is still a lot of debate among the public regarding the safety and efficacy promised by vaccine manufacturing companies, which cannot necessarily make people accept and be willing to pay for the vaccine. This research was conducted to determine and measure the attitude of the people of Magelang Regency in accepting and their willingness to pay for the Covid-19 vaccine if the vaccine is not provided free of charge by the government. Sampling was carried out on 400 respondents from the people of Magelang Regency using non-probability sampling using the convenience sampling method. Based on this research, it is known that the attitude of the respondents in this study is positive, but there are still people who are hesitant about getting the Covid-19 vaccination, especially if the vaccination is carried out every year. Likewise, the acceptance of the Covid-19 vaccine is quite good. In this research, it was also discovered that the majority of respondents did not agree that payment for vaccination was made individually or by insurance, and chose to do it for free/without paying. Lack of health education by medical personnel is the main factor causing respondents’ hesitation in responding and receiving vaccines.